2024
DOI: 10.3390/cancers16051008
|View full text |Cite
|
Sign up to set email alerts
|

Proton Treatment Suppresses Exosome Production in Head and Neck Squamous Cell Carcinoma

Ameet A. Chimote,
Maria A. Lehn,
Jay Bhati
et al.

Abstract: Proton therapy (PT) is emerging as an effective and less toxic alternative to conventional X-ray-based photon therapy (XRT) for patients with advanced head and neck squamous cell carcinomas (HNSCCs) owing to its clustered dose deposition dosimetric characteristics. For optimal efficacy, cancer therapies, including PT, must elicit a robust anti-tumor response by effector and cytotoxic immune cells in the tumor microenvironment (TME). While tumor-derived exosomes contribute to immune cell suppression in the TME,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Multiple elements of the tumor microenvironment also contribute to mechanisms to evade immune surveillance, including small tumor-derived extracellular vesicles, also known as exosomes [ 63 , 64 ]. A recent in silico paper by Chimote et al on primary HNSCC cells irradiated with 5 Gy PT or X-ray RT reported that PT lead to the production of 75% fewer exosomes compared to X-ray RT and non-irradiated HNSCC cells [ 65 ]. The inhibition of exosome production could highlight the advantages of PT over photon-based RT in enhancing anti-tumor immunity, as well as the potential benefits of combining PT with immune checkpoint inhibitors and various other forms of immunotherapy.…”
Section: New Insightsmentioning
confidence: 99%
“…Multiple elements of the tumor microenvironment also contribute to mechanisms to evade immune surveillance, including small tumor-derived extracellular vesicles, also known as exosomes [ 63 , 64 ]. A recent in silico paper by Chimote et al on primary HNSCC cells irradiated with 5 Gy PT or X-ray RT reported that PT lead to the production of 75% fewer exosomes compared to X-ray RT and non-irradiated HNSCC cells [ 65 ]. The inhibition of exosome production could highlight the advantages of PT over photon-based RT in enhancing anti-tumor immunity, as well as the potential benefits of combining PT with immune checkpoint inhibitors and various other forms of immunotherapy.…”
Section: New Insightsmentioning
confidence: 99%